#### Answer

$x =2$, $y =6$

#### Work Step by Step

$x + 2y = 14$
$3x + 5/4*y +5/4y = 21$
$x + 2y = 14$
$3x + 10/4*y = 21$ (combining like terms)
$x + 2y = 14$
$x + 2y-2y = 14-2y$
$x = 14-2y$ (isolating one variable)
$x = 14-2y$
$3x + 10/4*y = 21$
$3x + 10/4*y = 21$
$3*(14-2y) + 10/4*y = 21$ (substituting one variable for another)
$42 -6y +10/4*y = 21$
$42 -14/4*y = 21$ (combining like terms)
$42-14/4*y -42 = 21-42$ (eliminating the constant from one side of the equation)
$-14/4*y = -21$ (combining like terms)
$-14/4*y *-4/14 = -21*-4/14$ (eliminating the constant by the variable)
$y = 84/14 = 6$
$y=6$ (simplifying the constants)
$x +2y = 14$
$x + 2*6 = 14$ (substituting 6 for y)
$x +12 = 14$ (simplifying the equation)
$x + 12 - 12 = 14 - 12$ (eliminating the constant)
$x = 2$ (combining like terms)